Determination of Retinol, α-Tocopherol, Lycopene, and β-Carotene in Human Plasma Using HPLC with UV-Vis Detection: Application to a Clinical Study - Roman Kand’ár; Pavla Novotná; Petra Drábková (Journal of Chemistry)
A method is described here for the simultaneous determination of retinol, α-tocopherol, lycopene, and β-carotene in human plasma. The effectiveness of various protein precipitants and extraction solvents was tested. After adequate sample preparation, the samples were injected directly into the HPLC system. The separation was realized on an analytical reversed-phase column with a UV-Vis detection. The analytical performance of this method was satisfactory. The intraassay and interassay coefficients of variation were below 10%. The recoveries were as follows: 97.0% (CV 2.4%) for retinol, 94.6% (CV 1.7%) for α-tocopherol, 91.9% (CV 3.6%) for lycopene, and 93.9% (CV 4.2%) for β-carotene. The levels of selected fat-soluble vitamins in plasma of patients with cardiovascular disease were measured and discussed.